A Case Series of Patients Who Underwent Laparoscopic Extraperitoneal Radical Prostatectomy with the Simultaneous Implant of a Penile Prosthesis: Focus on Penile Length Preservation - Nicola Mondaini; Tommaso Cai; Enrico Sarti; Gaia Polloni; Andrea Gavazzi; Duccio Conti; Andrea Cocci; Maarten Albersen; Gianmartin Cito; Riccardo Bartoletti (The World Journal of Men's Health, 2018)
Purpose: There are many grey areas in the field of penile rehabilitation after radical prostatectomy (RP). The preservation of the full dimensions of the penis is an important consideration for improving patients’ compliance for the treatment. We present the first case series of patients treated by laparoscopic extraperitoneal RP and simultaneous penile prosthesis implantation (PPI) in order to preserve the full length of the penis and to improve patients’ satisfaction. Materials and Methods: From June 2013 to June 2014, 10 patients underwent simultaneous PPI (with an AMS InhibiZone prosthesis) and RP. Patients were evaluated by means of urological visits, questionnaires, and objective measurements before surgery, at discharge from the hospital, on postoperative days 21 to 28, each 3 months for the first year, and each 6 months thereafter. The main outcome measures were biochemical recurrence-free rate, penile length, and quality of life. Results: Ten patients (mean age of 61 years; completed the study follow-up period (median, 32.2 months). No difference was found between the time of surgery and the 2-year follow-up evaluation in terms of penile length. The pre-surgery 36-Item Short Form Health Survey (SF-36) median score was 97. Patients were satisfied with their penile implants, and couples’ level of sexual satisfaction was rated median 8. The median postoperative SF-36 score was 99 at 3 months follow-up. Conclusions: Laparoscopic extraperitoneal RP surgery with simultaneous PPI placement seems to be an interesting possibility to propose to motivated patients for preserving the length of the penis and improving their satisfaction.